NILAI KONTRIBUSI KEBUN BINATANG TERHADAP KONSERVASI SATWA, SOSIAL EKONOMI DAN LINGKUNGAN FISIK: STUDI KASUS KEBUN BINATANG BANDUNG - Puspitasari, Anggita; Masy'ud, Burhanuddin; Sunarminto, Tutut (Department of Forest Resources Conservation and Ecotourism - IPB University, 2016)
The existence of zoos basically have an important and strategic role, and is expected to contribute significantly to aspects of wildlife conservation, socio-economic and physical environment. Bandung Zoo (KBB) as one of the long-standing zoos has contributed greatly to the surrounding environment, making it suitable to be used as a case study in this research. The purposes of this study were to assess the contribution value of Bandung Zoo (KBB) seen from the aspect of wildlife conservation, social, economic and physical environment, as well as determine the contribution rate of Bandung Zoo (KBB) as a conservation organization. Data on this research collected by literature study, interview, and field oservation.. Performance evaluation of all aspects of Bandung Zoo (KBB) contribution is at 62,69 which is considered as low value, so the implication is the need for improvement in the management of Bandung Zoo (KBB). Wildlife conservation is an aspect that need to be given priority because its very low level of contribution (23,69), particularly on animal welfare because it affects the success of breeding and support to the in situ conservation efforts through a wildlife reintroduction into their natural habitats. Social and economic aspects are in moderate level (23,04), because, the support of the manager in the open access to the surrounding community in setting up businesses and employment is not optimal yet. Aspect of the physical environment is in moderate level of contribution (16,25), this is because types of vegetation found in Bandung Zoo (KBB) are not optimal (20-30%) to absorb and adsorb dust and pollutants. Keywords: animal conservation, contributions, physical environment, socio-economic